2016
DOI: 10.1590/s1806-37562015000000216
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator response cut-off points and FEV 0.75 reference values for spirometry in preschoolers

Abstract: Objective:To determine the cut-off points for FEV1, FEV0.75, FEV0.5, and FEF25-75% bronchodilator responses in healthy preschool children and to generate reference values for FEV0.75. Methods:This was a cross-sectional community-based study involving children 3-5 years of age. Healthy preschool children were selected by a standardized questionnaire. Spirometry was performed before and after bronchodilator use. The cut-off point of the response was defined as the 95th percentile of the change in each parameter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
4
0
4
Order By: Relevance
“…Two studies of collated epidemiological data in healthy adults reported the upper limit (95% percentile) of the range of responses in healthy individuals of the BDR to be 11.6% and 10.1% of predicted for FEV1 and 10.2% and 9.6% of predicted for FVC (59,62). Similar changes of 8.5% for FEV0.75 in young children have been reported (65). BDR in FVC, rather than FEV1, has been shown to better reflect the physiological processes of air trapping (66)(67)(68)(69)(70).…”
Section: Expressing the Results Of A Bronchodilator Responsiveness Testsupporting
confidence: 53%
“…Two studies of collated epidemiological data in healthy adults reported the upper limit (95% percentile) of the range of responses in healthy individuals of the BDR to be 11.6% and 10.1% of predicted for FEV1 and 10.2% and 9.6% of predicted for FVC (59,62). Similar changes of 8.5% for FEV0.75 in young children have been reported (65). BDR in FVC, rather than FEV1, has been shown to better reflect the physiological processes of air trapping (66)(67)(68)(69)(70).…”
Section: Expressing the Results Of A Bronchodilator Responsiveness Testsupporting
confidence: 53%
“…Los niños menores de 6 años aún tienen su pulmón en etapa de crecimiento, las vías aéreas son relativamente más grandes que el parénquima pulmonar, lo que explicaría un vaciamiento rápido con la espiración forzada, con un final brusco y precoz 8,11,27 . Los niños a esta edad pueden expresar su CVF con espiraciones menores a 1 segundo, obteniendo valores de VEF 0,5 y VEF 0,75 , los cuales tienen buena reproducibilidad y son útiles para evaluar respuesta a broncodilatador [28][29][30]37 .…”
Section: Discussionunclassified
“…En la curva flujo/volumen: se pueden aceptar curvas con final abrupto, siempre que el valor en el que cesa el flujo espiratorio sea menor al 10% del FEM (Figura 3) (4, 13,15,17,19,21,22). Las curvas con cese del flujo mayor al 10% del FEM se las clasifica como de terminación prematura y de ellas solo se puede obtener VEFt (volumen espirado forzado en el tiempo, el que puede ser VEF1, VEF0,5 o VEF0,75) y FEM, no permite evaluar otros flujos ni CVF (Figura 4) (21) (Figura 4).…”
Section: Del Final De La Curvaunclassified
“…Si bien lo que se considera como respuesta al broncodilatador varía levemente entre los distintos estudios, se sugiere interpretar como respuesta significativa (diferencia entre el valor basal y el obtenido luego de inhalar con 400mcg de salbutamol), a un cambio de al menos 12% en VEFt y 35% en FEF 25-75. Este último siempre que se mida a isovolumen, o sea con una diferencia menor al 5% en la CVF entre la curva pre y post broncodilatador (10,17,22,30). Aunque la curva tenga una finalización temprana, si el niño pudo realizar VEF0,5 se puede interpretar la respuesta al broncodilatador (22).…”
Section: Interpretaciónunclassified
See 1 more Smart Citation